Gratitude pada Female Breadwinner di Kelurahan 3 Ilir Palembang - Natallija Butar Butar; Dwi Hurriyati (Fakultas Psikologi Universitas Pancasila, 2022)
This research aims to determine the type of mother’s gratitude who is the breadwinner for her family, and the factors that influence their gratitude at Kelurahan 3 Ilir Palembang. The difference between this study and previous research is that previous research tended to examine the psychological dynamics of the subject so that the scope is broad. Therefore, this research is oriented to the types and factors of gratitude so that the scope of the research is more specific. The sampling technique used is purposive sampling. The subjects were 2 women who married and have children, also became female breadwinners in their families. This research uses a qualitative method with a phenomenological approach. The results showed that both subjects had gratitude as female breadwinners. The YL type of gratitude is transpersonal, while the ED gratitude is personal. Then the factors that affect YL's gratitude are emotionality and religiousness. Meanwhile, gratitude ED is influenced by emotionality and prosociality. So it can be concluded that there are differences in the type and factor of gratitude on the subject.